ГЕНЕЗА ВПРОВАДЖЕННЯ ІНФОРМАЦІЙНО-КОМУНІКАЦІЙНИХ ТЕХНОЛОГІЙ У ФІЗИЧНІЙ ОСВІТІ: ВІД КОМП’ЮТЕРНОЇ ПІДТРИМКИ НАВЧАННЯ ДО ФОРМУВАННЯ КЛЮЧОВИХ І ПРЕДМЕТНИХ КОМПЕТЕНТНОСТЕЙ - Holovko, Mykola V. (Information technologies and learning tools, 2015)
In the article, the peculiarities of the process of the implementation of the information and communication technologies in teaching Physics, the development of the computer didactic provision are specified on the basis of the historical and methodological analysis. The development of the scientific fundamentals and the tools of their implementation in the homeland theory and methodology of teaching Physics, the impact of the formation of the computer-oriented environment as well as the qualitative change in the academic process subjects’ role are demonstrated. The necessity of the further didactic researches on the abovementioned issue because of the priority of the computer-oriented technologies in the formation of the key and the subject competences of the comprehensive and high school pupils in the process of Physics teaching are actualized. В статье на основе историко-методического анализа обосновываются особенности процесса внедрения информационно-коммуникационных технологий в обучение физики, развитии компьютерного дидактического обеспечения. Освещается развитие научных основ и механизмов их реализации в отечественной теории и методике обучения физике, влияние на формирование компьютерно-ориентированной среды и качественное изменение роли субъектов учебного процесса. Актуализируется целесообразность дальнейших дидактических исследований этой проблемы в связи с приоритетностью компьютерно-ориентированных технологий в формировании ключевых и предметной компетентности учащихся общеобразовательной и высшей школы в процессе обучения физике. У статті на основі історико-методичного аналізу обґрунтовуються особливості процесу впровадження інформаційно-комунікаційних технологій у навчання фізики, розвитку комп’ютерного дидактичного забезпечення. Висвітлюється ґенеза наукових засад і механізмів їх реалізації у вітчизняній теорії і методиці навчання фізики, вплив на формування комп’ютерно-орієнтованого середовища і якісну зміну ролі суб’єктів навчального процесу. Актуалізується доцільність подальших дидактичних досліджень означеної проблеми у зв’язку з пріоритетністю комп’ютерно-орієнтованих технологій у формуванні ключових і предметної компетентностей учнів загальноосвітньої і вищої шкіл у процесі навчання фізики.